2015
DOI: 10.1051/swsc/2015032
|View full text |Cite
|
Sign up to set email alerts
|

The heliospheric Hale cycle over the last 300 years and its implications for a “lost” late 18th century solar cycle

Abstract: A Hale cycle, one complete magnetic cycle of the Sun, spans two complete Schwabe cycles (also referred to as sunspot and, more generally, solar cycles). The approximately 22-year Hale cycle is seen in magnetic polarities of both sunspots and polar fields, as well as in the intensity of galactic cosmic rays reaching Earth, with odd-and even-numbered solar cycles displaying qualitatively different waveforms. Correct numbering of solar cycles also underpins empirical cycle-to-cycle relations which are used as fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Other authors such as [16], [17], [18] have obtained similar periodicities between solar indices and climatic parameters. It has been reported that solar activity varies between active and quiet phases with 11 year solar cycle known as Schwabe cycle, 22 year polarity reversals called Hale cycle and 80 year cycle known as Gleissberg cycle [19], [20]. The Schwabe, Hale, and Gleissberg cycles can be stretched or shortened, leading to different harmonics [21].…”
Section: Resultsmentioning
confidence: 99%
“…Other authors such as [16], [17], [18] have obtained similar periodicities between solar indices and climatic parameters. It has been reported that solar activity varies between active and quiet phases with 11 year solar cycle known as Schwabe cycle, 22 year polarity reversals called Hale cycle and 80 year cycle known as Gleissberg cycle [19], [20]. The Schwabe, Hale, and Gleissberg cycles can be stretched or shortened, leading to different harmonics [21].…”
Section: Resultsmentioning
confidence: 99%
“…Five independent sets of data would yield a standard deviation of ~5.5% for the annual paleocosmic ray data, 0.3 nT for the annual estimates of the heliospheric magnetic field near Earth, and would allow smaller solar energetic particle events to be detected and eliminated from B[GCR‐MB2]. It would also permit the time profile of the 11 year cycle in the PCR to be determined for individual cycles (“sharp rising ” or “flat topped”) thereby identifying the polarity of the solar dipole into the past [ Potgieter , ; Owens et al , ]. Extending the annual PCR record back to 1000 before present (B.P.). (950 Common Era (C.E.))…”
Section: Comparison With Cosmogenic Radionuclide Reconstructionsmentioning
confidence: 99%
“…Researchers have shown that solar activity alternates between active and quiet phases with an average duration of 11 year (Schwabe cycle), 22 year solar magnetic cycle polarity reversals (Hale cycle) and probably an ~80 year cycle (Gleissberg cycle), with short term periodicities (Nayar, 2006;Kane, 2005;El Mallah and El Sharkawy, 2011;Nagaya et al, 2012;Owen et al, 2015). The Schwabe, Hale and Gleissberg cycles can be stretched/shorten, leading to different harmonized (Miyahara et al, 2009).…”
Section: Resultsmentioning
confidence: 99%